Examining Working Memory Performance in Adult Psychosomatic Inpatients - Held, Judith; Ramadani, Laura; Vîslă, Andreea; Köllner, Volker; Hilpert, Peter; Flückiger, Christoph (Frontiers in Psychology, 2021)
Background: There is cumulating evidence that working memory (WM) processing is impaired in individuals suffering from a psychosomatic and a psychological disorder. However, it is unclear how repetitive negative thinking (RNT), depressive symptoms and patient characteristics (i.e., age, incapability to work) contribute to WM impairments. The present study examines how these factors affect WM performance in highly distressed adult psychosomatic inpatients. Methods: Seventy-six inpatients (Mage = 52.7, SD = 8.4) from a psychosomatic rehabilitation clinic performed a two-block WM updating task, with accuracy and reaction time as indicators of WM functioning. Results: Multivariate mixed effect model results show that accuracy and reaction time significantly decreased from WM Block 1 to WM Block 2. Higher levels of RNT, more severe depressive symptoms and higher age were associated with worse WM accuracy in Block 1. None of these variables were significantly associated with WM reaction time (in Block 1). Conclusion: From a clinical perspective, the results suggest that screening for the presence of high RNT levels, severe depressive symptoms or higher age may help to identify patients with impaired WM functioning and to intervene on these important patient characteristics early in the rehabilitation process.